Description of Schizophrenic Patients in Controlling Hallucinations in Mental Hospitals in Indonesia - PH, Livana; Mulyani, Sri; Suerni, Titik; Ardianti, Yulia (PT Saintek Medika Nusantara, 2024)
Nowadays, many people feel that they are not accepted or failed in an environment, is unable to control his emotions so that the client feels disturbed and changes behavior marked by the appearance of delusions, thought process disorders and hallucinations. The purpose of the study was to determine the patient’s ability to control hallucinations. This research design is a descriptive study research, quantitative research type. The sample of this study amounted to 27 respondents with a purposive sampling technique. The measuring instrumen uses an hallucination control questionnaire that is valid and reliable. Univariate analysis data using frequency distribution. The results showed that the majority of patients were best able to control hallucinations by rebuking them.